The Role оf Information Space in the Development оf Civil Society (Herald of Journalism, 2019)
This article examines the role and importance of the media in the development of civil society in Kazakhstan. Here studied and evaluated opinions of scientists in the study of civil society from ancient times of antiquity, examples of works of famous thinkers and philosophers, like Plato, Aristotle, Chernilovsky, Machiavelli, Hayek, Fichte, Schelling, Hegel, Black, Garamshi, Michnik, Bobbio, Hobermas and Arato are given.Based on the experience of leading world countries in the development of civil society, where the law is considered as the main value, the elements of freedom of speech, separation of powers, equality before the law, etc. are considered in detail and diversified in this scientific work. Conditionally stopped at the three levels within its structure, such requirements as a developed democratic system, a sociallystructural system, an open system were studied at the proper level, was touched upon the subject ofhuman values, which is the center and the most important factor of civil society. It is about the developmentof civil society through state cooperation together with non-governmental organizations, as well asthe activities of the media in this process.Freedom of speech of the press in civil society is considered as the main principle, explaining therole of mass media for collective-agitation, collective-organizational goals and objectives. It has beenproven that the core of creation and development of civil society institutions are the media indicatorproperties. Here given intensive surveys, modern aspirations of the mass media of Kazakhstan in thisdirection, mechanisms of development and promotion of civil society ‒ the importance of politics, science,culture, economics, etc., the symptoms and prerequisites for the development of modern mediaare sorted in accordance with the requirements of the market.It is based on why the development of civil society cannot remain outside the direct dependenceon the information space, since information is the main factor of socio-economic development. After all,through the media, information is provided about various spheres of social and political, economic andsocial orientation, including the promotion of initiatives in the development of civil society. Therefore,a research article is comprehensively describes activities of the information space of Kazakhstan, whichis useful in the development of civil society institutions.
Keywords: civil society, information space, information, media, journalism.